UK cardiac rehabilitation fit for purpose? A community-based observational cohort study. Issue 10 (10th October 2020) - Ibeggazene, Saïd; Moore, Chelsea; Tsakirides, Costas; Swainson, Michelle; Ispoglou, Theocharis; Birch, Karen
Abstract : Objectives: This study aimed to characterise the exercise performed in UK cardiac rehabilitation (CR) and explore relationships between exercise dose and changes in physiological variables. Design: Observational cohort study. Setting: Outpatient community-based CR in Leeds, UK. Rehabilitation sessions were provided twice per week for 6 weeks. Participants: Sixty patients (45 male/15 female 33–86 years) were recruited following referral to local outpatient CR. Outcome measures: The primary outcome was heart rate achieved during exercise sessions. Secondary outcomes were measured before and after CR and included incremental shuttle walk test (ISWT) distance and speed, blood pressure, brachial artery flow-mediated dilatation, carotid arterial stiffness and accelerometer-derived habitual physical activity behaviours. Results: The mean % of heart rate reserve patients exercised at was low and variable at the start of CR (42%±16 %) and did not progress by the middle (48%±17 %) or end (48%±16 %) of the programme. ISWT performance increased following CR (440±150 m vs 633±217 m, p<0.001); however, blood pressure, body weight, endothelial function, arterial stiffness and habitual physical activity behaviours were unchanged following 6 weeks of CR (p>0.05). Conclusion: Patients in a UK CR cohort exercise at intensities that are variable but generally low. The exercise dose achieved using this CR format appears inadequate to impact markers of health. Attending CR had no effect on physical activity behaviours. Strategies to increase the dose of exercise patients achieve during CR and influence habitual physical activity behaviours may enhance the effectiveness of UK CR.